Extra virgin olive oil mitigates lung injury in necrotizing enterocolitis: Effects on TGFβ1, Caspase-3, and MDA in a neonatal rat model - Mustafa Tuşat; Recep Eröz; Ferhan Bölükbaş; Erkan Özkan; Mehmet Semih Demirtaş; Hüseyin Erdal; Osman Okan Özocak (PLoS ONE, 2025)
Background Necrotizing enterocolitis (NE), which is common in premature babies, has been associated with lung damage. Our aim is to explore the effect of enterally administered extra virgin olive oil (EO) with rich polyphenol content on clinical parameters, histopathological score, Transforming growt factor beta-1 (TGFβ1), Caspase 3 and Malondialdehyde (MDA) levels in NE-related lung injury of neonatal rats. Methods Three groups (control, NE, NE+EO) were created, with 8 neonatal rats in each group. NE was induced by hypoxia-hyperoxia-hypothermia and formula feeding. EO was given to the treatment group by orogastric probe for 3 days. Intestinal and lung tissue were excised for analysis. Results TGFβ1 expression levels, TGFβ1 and MDA concentration levels were higher in the NE compared to NE +  EO and control groups (p < 0.001), and their levels decreased after EO treatment compared to the NE group (p < 0.001). It was determined that EO treatment significantly reduced the histopathological damage and the caspase-3 (CASP3) expression level in the lung (p < 0.001). Conclusion Our findings emphasize that TGFß1 has an crucial function in NE-related lung injury and that EO has therapeutic potential in NE-related lung injury.